Domibacillus enclensis sp nov., isolated from marine sediment, and emended description of the genus domibacillus - Sonalkar, Vidya V.; Mawlankar, Rahul R.; Krishnamurthi, Srinivasan; Tang, Shan-Kun; Dastager, Syed Gulam (International Journal of Systematic and Evolutionary Microbiology, 2014)
A novel red-pigmented bacterial strain, designated NIO-1016(T), was isolated from a sediment sample from Chorao Island, India and was investigated by a polyphasic taxonomic approach. The strain was Gram-reaction-positive, strictly aerobic, motile and catalase-positive and produced spherical to slightly ellipsoidal endospores with subterminal position on swollen sporangia. The genomic DNA G+C content was 46.9 molok. The major fatty acids were anteiso-C-15:0, anteiso-C-17:0, iSO-C-15:0 and C-16:0. The predominant quinones were MK-6 (89.3 %) and MK-7 (8.7 %). The polar lipids consisted of diphosphatidylglycerol, phosphatidylglycerol, and an unidentified phospholipid. meso-Diaminopimelic acid (type My) was present in the cell-wall peptidoglycan and the major whole-cell sugars were glucose and ribose. The closest phylogenetic neighbours were identified as Domibacillus robiginosus DSM 25058(T) (98.0% similarity) and Domibacillus indicus DSM 28032(T) (97.2% similarity), other species of the genus Bacillus displayed below 96% similarity. Phylogenetic, physiological, biochemical and morphological differences between strain NI0-1016(T) and its closest neighbours indicate that this strain represents a novel species in the genus Domibacillus in the family Bacillaceae for which the name Domibacillus enclensis sp. nov. is proposed with the type species N10-1016(T) (=DSM 25145(T)=NCIM 5462(T)=CCTCC AB 2011121(T)).

Domibacillus mangrovi sp nov and domibacillus epiphyticus sp nov., isolated from marine habitats of the central west coast of India - Verma, Ashish; Ojha, Anup Kumar; Dastager, Syed G.; Natarajan, Rameshkumar; Mayilraj, Shanmugam; Krishnamurthi, Srinivasan (International Journal of Systematic and Evolutionary Microbiology, 2017)
While studying culturable bacterial diversity in different marine habitats of the central west coast of India, two novel Gramstain-positive, strictly aerobic, motile, endospore-forming and rod-shaped bacterial strains designated as SAOS 44(T) and SAB 38(T) were isolated from mangrove sediment soil and the surface of a macroalga, respectively. The strains were taxonomically characterized by using a polyphasic approach and genomic methods. The phylogenetic analysis based on 16S rRNA gene sequencing placed the strains firmly in the genus Domibacillus and were most closely related to Domibacillus antri KCTC 33636(T). The predominant fatty acids were iso-C-15 : 0 and anteiso-C-15 : 0. The major polar lipids were diphosphatidylglycerol and phosphatidylglycerol in addition to an aminophosphoglycolipid. MK-6 was the only respiratory quinone. The range of values of digital DNA-DNA hybridization (19.2-24.9 %) and the ortho-average nucleotide identity (74.1-81.4 %) among strains SAOS 44(T), SAB 38(T) and other Domibacillus species clearly supports their status as a distinct and novel species for which the names Domibacillus mangrovi sp. nov. SAOS 44(T) (=DSM 100930(T)=KCTC 33820(T)=MTCC 12571(T)) and Domibacillus epiphyticus sp. nov. SAB 38(T) (=DSM 100929(T)= KCTC 33830(T)=MTCC 12575(T)) are proposed, respectively.